Weapons of Resistance: The Material Symbolics of Postclassic Mexican Spinning and Weaving. Issue 4 (December 2019) - McCafferty, Geoffrey G.; McCafferty, Sharisse D.
Abstract : Material culture studies demonstrate how objects may act to communicate information regarding social identity. In this study we consider ethnohistorical, ethnographic, and archaeological evidence for Postclassic spinning and weaving as symbols relating to female ideology in ancient Mexico. We then relate a contextual interpretation of texts and images to contemporary symbolism, particularly associated with members of the female earth/fertility deity complex depicted and described in precolumbian and early colonial pictorial manuscripts. For our case study we analyze decorative imagery found on baked-clay spindle whorls from Postclassic Cholula, Mexico. This collection is representative of an iconographic system relating to female ideology. Whorls, as well as other spinning and weaving tools, paralleled male-oriented weapons to create a symbolic equivalence or, as we argue, a usurpation of the male symbols within a female worldview as a form of resistance to male domination. We conclude that the symbolic system used on spindle whorls and in other aspects of female practice created a communication network understood by Postclassic women.